2017
DOI: 10.17096/jiufd.31921
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive System Affects Repair Bond Strength of Resin Composite

Abstract: Purpose:This study evaluated the effects of different adhesive systems on repair bond strength of aged resin composites.Materials and Methods:Ninety composite discs were built and half of them were subjected to thermal aging. Aged and non-aged specimens were repaired with resin composite using three different adhesive systems; a two-step self-etch adhesive, a two-step total-etch adhesive and a one-step self-etch adhesive; then they were subjected to shear forces. Data were analyzed statistically.Results:Adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 29 publications
1
20
1
2
Order By: Relevance
“…Studies involving Clearfil SE Bond, a self-etching adhesive, showed that this material provided greater bond strength than other types of adhesive systems. The authors attributed those results to the presence of 10-MDP (18,23). Clearfil SE Bond, unlike Single Bond Universal, is a two-step system.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies involving Clearfil SE Bond, a self-etching adhesive, showed that this material provided greater bond strength than other types of adhesive systems. The authors attributed those results to the presence of 10-MDP (18,23). Clearfil SE Bond, unlike Single Bond Universal, is a two-step system.…”
Section: Discussionmentioning
confidence: 96%
“…Water absorption has a negative effect on composite restoration, causing a reduction in resistance to wear, residual monomers and hydrolytic degradation of chemical reactions (17). According to some authors, the highest water absorption occurs in the first week, and in up to two weeks, it is still possible to obtain chemical adhesion of new composite increments due to the presence of free radicals available in the old composite (18).…”
Section: Discussionmentioning
confidence: 99%
“…In the no water storage groups, BE2 and APX, there were no significant differences in µSBS between with and without the application of one-step selfetch adhesive (Clearfil SE One). The application of an adhesive agent could improve the surface wettability on the cured-composite and enhance monomer diffusion into the cured-composite, leading to an increase in repair bond strength 20) . However, in the no waterstorage group, the existence of un-reacted monomers in the cured-composite would not require the diffusion of further additional monomers with adhesive application into the cured-composite to obtain composite-composite adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Clearfil SE One contains the hydrophilic monomer, HEMA. Therefore, adhesive application could enhance monomer diffusion into the water-aged cured-composite with few unreacted monomers and improves surface wettability for application of the hydrophobic composite 20) .…”
Section: Discussionmentioning
confidence: 99%
“…The success of these procedures mainly depends on the composite resin adhesion to the artificial teeth [7]. Various methods have been reported to improve the reactivity of highly converted composites; these methods include acid etching [9], air abrasion [10] and the use of adhesives [11]. There is no consensus on the results obtained with the different procedures.…”
mentioning
confidence: 99%